(untitled) (Fiep Bulletin - online, 2014)
The measurementofphysical fitness Of individual swith the focus on their functional classification has been studied since 1918 ,when it was performed the first stress test . There is a wide variety of exercise tests to predict VO2 max performed in the field. The aimof this study was correlate the values ??of maximu moxygen consumption( VO2max ) , obtained in two protocol sindirect sub – field maximum . Protocols were used Cooper 12 minutes and2,400 ,seeking the possibility of using the results in prescribing exercise intensities for physically active individuals - not athletes . The sample consisted of 15 subjects( four male andeleven female ) physically active , with 33 ± 11.6 years of age, 71 ± 26.1 body mass , 155 ± 28.2 cm in height . The protocols used were performed in all subjects ,with an interval between one and a not her one week. Besides descriptives tatistics ,we used the Pearson correlation . The result of the correlation coefficientis Pearson’s product moment r = 0.88 , it means that there is a strong positive correlation between the two protocols used , or suggested that both protocols can be used to predict the aerobic capacity, . Based on the results presented it is concluded that the administration of these field protocols showed no significant difference for the prediction of maximum oxygen consumption , not interfere in the subsequent decision decision to prescribe aerobic training intensity .